2006
DOI: 10.1007/s00251-005-0064-3
|View full text |Cite
|
Sign up to set email alerts
|

Immune-related, lectin-like receptors are differentially expressed in the myeloid and lymphoid lineages of zebrafish

Abstract: The identification of C-type lectin (Group V) natural killer (NK) cell receptors in bony fish has remained elusive. Analyses of the Fugu rubripes genome database failed to identify Group V C-type lectin domains (Zelensky and Gready, BMC Genomics 5:51, 2004) suggesting that bony fish, in general, may lack such receptors. Numerous Group II C-type lectin receptors, which are structurally similar to Group V (NK) receptors, have been characterized in bony fish. By searching the zebrafish genome database we have ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…The inability of pre-E11 AGM cells, which have been shown to possess multilineage (including lymphoid) differentiation capacity in vitro , to engraft adult animals may thus be due to immune rejection via natural killer (NK) cells that are highly radioresistant (Waterfall et al, 1987) and efficiently destroy MHCI-deficient cells (Lanier, 2005). Surface molecules related to mammalian NK receptors are expressed in zebrafish leukocytes (Panagos et al, 2006), suggesting that improved methods to ablate host NK cells may result in improved donor cell engraftment.…”
Section: Research Articlementioning
confidence: 99%
“…The inability of pre-E11 AGM cells, which have been shown to possess multilineage (including lymphoid) differentiation capacity in vitro , to engraft adult animals may thus be due to immune rejection via natural killer (NK) cells that are highly radioresistant (Waterfall et al, 1987) and efficiently destroy MHCI-deficient cells (Lanier, 2005). Surface molecules related to mammalian NK receptors are expressed in zebrafish leukocytes (Panagos et al, 2006), suggesting that improved methods to ablate host NK cells may result in improved donor cell engraftment.…”
Section: Research Articlementioning
confidence: 99%
“…A single nitr13 and two alternatively spliced nitr14a cDNAs were amplified via 3′ RACE using nested, overlapping primers (and touch-down PCR as described (Panagos et al 2006). The sequence of the primary and nested primers for nitr13 RACE were: 5′-ATGAGAATCGTGTGGATTTCTCTCATG-3′ and 5′-GGATTTCTCTCATGCTTCTATGCAGG-3′, respectively.…”
Section: Rapid Amplification Of Cdna Ends (Race)mentioning
confidence: 99%
“…In fact, it has recently been shown that lectins like Dectin-1 (Rogers et al 2005) and DC-SIGN (Geijtenbeek et al 2003) can synergize with TLRs and function as co-receptors to modulate host responses to infections. Several C-type lectins have been identified in the zebrafish, including the mannose-binding lectins (Vitved et al 2000) and the Group II immune-related, lectin-like receptors (Illrs; Panagos et al 2006). Each of the Illrs is predicted to possess a C-type lectin-like domain, a coiled-coil domain, a transmembrane domain, and one or two ITIM or ITIM-like cytoplasmic domains (Panagos et al 2006).…”
Section: Additional Innate Immunity Receptors In Zebrafishmentioning
confidence: 99%
“…Several C-type lectins have been identified in the zebrafish, including the mannose-binding lectins (Vitved et al 2000) and the Group II immune-related, lectin-like receptors (Illrs; Panagos et al 2006). Each of the Illrs is predicted to possess a C-type lectin-like domain, a coiled-coil domain, a transmembrane domain, and one or two ITIM or ITIM-like cytoplasmic domains (Panagos et al 2006). The presence of these ITIM or ITIM-like sequences indicate a likely role in inhibiting downstream signaling; however, it has been observed that in two of these lectins, Illr3a and Illr3b, there is an arginine residue in the transmembrane domain (Panagos et al 2006).…”
Section: Additional Innate Immunity Receptors In Zebrafishmentioning
confidence: 99%